The use of X-ray for quantifying lead shot pellets in substrate samples - Milne, H; Ramsay, N F (Wildfowl, 1987)
X-radiography was used to detect lead pellets in intertidal mud samples. The samples, removed by a corer, were sieved and searched by eye for lead, with a mean search time of 9 minutes (range 5-20 minutes). A total of 18 pellets were found in 32 samples. The samples were then placed upon X-ray sensitive paper and X-rayed for 1-2 minutes. Forty-three pellets were recorded on the radiographs. Subsequently the samples were re-checked and all 43 pellets were found. Mean search time required was 15 minutes (range 9-25 minutes). The technique indicates a large potential source of error in conventional methods used to find lead in mud samples. Unsieved mud samples and pellets fixed beneath stones were also X-rayed. In all cases the pellets were detectable, Gizzard grit samples were also analysed in this way.